Clinical and ultrasound predictors of clinically significant endometrial pathology in women with histologically confirmed lesions: a retrospective case–control study - Xiao Yuhong; Wang Bolun; Wang Xiliang; Yan Li; Yu Tingting; Xiu Yinling; Yuexin Yu; Ma Xiangwei (Frontiers in Oncology, 2026)
Objective To identify clinical and ultrasound predictors of clinically significant endometrial pathology and to develop an internally validated clinicosonographic model in women with histologically confirmed endometrial or intracavitary lesions. Methods This unmatched retrospective case–control study included women with histologically confirmed lesions who had complete clinicosonographic data. All eligible women with clinically significant pathology during the study period were included (n=500), and a random 1:1 sample of eligible benign-pathology controls was selected. The primary outcome was clinically significant pathology, defined as endometrial intraepithelial neoplasia (EIN)/atypical hyperplasia or endometrial carcinoma. Univariable and multivariable logistic regression analyses were performed to evaluate clinical and sonographic predictors. Three prespecified models were developed: clinical, sonographic, and combined clinicosonographic models. Model discrimination was assessed using the area under the receiver operating characteristic curve (AUC), and internal validation was performed with bootstrap resampling. Results Compared with benign pathology, clinically significant pathology was associated with older age, lower parity, greater endometrial thickness, larger lesion size, mixed/heterogeneous echogenicity, abnormal endomyometrial junction, higher Color Doppler flow imaging [CDFI] score, and more frequent polypoid mass-like morphology, while the bright-edge sign was more common in benign pathology. In the final combined model, independent predictors of clinically significant pathology were age (adjusted odds ratio [aOR] per 5-year increase 11.49, 95% confidence interval [CI] 8.10–16.28), parity (aOR per additional birth 0.63, 95% CI 0.53–0.75), endometrial thickness (aOR per 5-mm increase 1.98, 95% CI 1.55–2.53), lesion length (aOR per 1-mm increase 1.52, 95% CI 1.29–1.80), mixed/heterogeneous echogenicity (aOR 1.87, 95% CI 1.13–3.09), abnormal endomyometrial junction (aOR 1.80, 95% CI 1.14–2.83), minimal/moderate/abundant CDFI score versus none, bright-edge sign (aOR 0.37, 95% CI 0.20–0.66), and polypoid mass-like lesion (aOR 3.85, 95% CI 2.42–6.12). The combined model showed the best discrimination, with an AUC of 0.959 and optimism-corrected AUC of 0.957. Conclusions Clinically significant endometrial pathology is associated with a distinct clinicosonographic profile that includes older age, lower parity, thicker endometrium, larger lesions, heterogeneous echogenicity, junctional abnormality, increased vascularity, and polypoid mass-like morphology, whereas the bright-edge sign appears reassuring. A combined clinical and ultrasound model showed excellent internal discrimination and may help structure risk assessment in women with pathology-confirmed endometrial or intracavitary lesions.